A comparison of the metals and metalloid levels in wild and cultured Capoeta damascina fish and assessment of its potential health risks to humans in Iran. (2nd October 2022) - Monji, Hadi; Nematollahi, Amin; Copat, Chiara; Ferrante, Margherita; Fallah, Aziz A.
Abstract: This research aimed to assess metals/metalloids (Fe, Cr, Cu, Mn, Mo, Se, Zn, Ni, Sr, Ba, Co, Hg, Pb, As, and Cd) in liver and muscle tissue of wild and culture Capoeta damascina fish using (ICP/OES). The healthy assessment revealed that the accumulation of Hg in adults and children consuming 7 meals/week might harm their health. However, the high Se/Hg ratio in the fish alleviates the adverse effects of Hg. Furthermore, the carcinogenic risk of As and Ni accumulation should be considered for adults having 7 meals/week or more. It is recommended to continually monitor these metals and metalloids in the fish and cultured fish feed.